PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DANRASIO PROFITABILITAS TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sulistiana, Indra (Universitas Serang Raya, 2017)
This study aimed to examine the effect of disclosure of social responsibility (Corporate Social Responsibility) and profitability ratio to the stock price. Samples were selected by purposive sampling method, as many as 23 manufacturing companies in chemical and basic industries. This study uses multiple regression analysis to test the hypothesis. However, previous test is conducted prior to classical assumption. The test results together against the hypothesis shows there are influence between coporate social responsibility disclosureon stock prices. The test results show that Ha1partially accepted, which means thereis influence between coporate social responsibility disclosure on stock prices while Ha2 rejected because t arithmetic < t table, which means there is no effect between profitability to stockprices. Keywords: corporate social responsibility, profitability, stock prices.